As implicações do programa 'São Paulo faz escola' no trabalho docente de professores iniciantes: um estudo de caso - Barros, Ricardo Abdalla [UNESP] (2014)
This study tried to propitiate reflections about teaching work of the teachers in the teaching of Portuguese Language and Literature area who work in the context of São Paulo state school with the implementation of the curriculum alteration by use of books in teaching activities – the Program São Paulo faz escola. For this we conducted a qualitative research through a case study in a public school in a city of countryside of the state of São Paulo, with three teachers who work in High School, in this area of knowledge, who were inserted like users of the above-mentioned material. In this study the accompaniment of these teachers was conducted in the first semester of 2013 through observations of classes, interviews and documental analysis of the activities performed in these classes, as well as the Curriculum Proposal of the State of São Paulo. Before the done work we point that, for teachers, this curriculum change impacted the classes of these teachers, because the curriculum impose, in many cases, the form and conception of teaching and learning that they should take forward the use of the books. It is visible, in the analyzed data, the feeling that was take away the authorship and the autonomy of professional intervention of these teachers, getting a teaching job in a much more utilitarian perspective of a predetermined curriculum. Moreover, we observe the daily pressure that the teachers suffer for the students can show high scores in purely quantitative exams of the instruments used by State Department of Education, disregarding completely the process and their own challenges experienced during the school year